PENGARUH ARUS KAS DAN PENGEMBALIAN MODAL TERHADAP NILAI PERUSAHAAN (Studi Pada PT. Hero Supermarket, Tbk Periode 2004 ??? 2018) - Rida Ristiyana (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2019)
The purpose of this study to determine the effect of cash flow and return on capital on firm value at PT. Hero Supermarket, Tbk. The cash flow has a cash ratio proxy, return on capital has a ROE (Return on Equity) proxy and firm value has an EPS proxy (Earning Per Share). The sample of this study was PT. Hero Supermarket, Tbk which submits annual financial reports from the period 2004-2018. The technique of data collection used library study and field survey with the data of observational (n) = 12. The analytical tool used Multiple Linear Regression. The results of this study, cash ratio has given negative and significant impact on earnings per share, but return on equity has given positive and significant impact on earnings per share.Both, the cash ratio, return on equity showed significantly influence to the earnings per share.